Structure and in vitro antioxidant and immunomodulatory activity of a glucan from the leaves of Cyclocarya paliurus - Sichen He; Jin Yan; Lingli Chen; Hui Chen; Wenjun Wang (Journal of Functional Foods, 2024)
In this study, a novel polysaccharide (CPP-80) was prepared from the leaves of Cyclocarya paliurus and its detailed structure, antioxidant and immunomodulatory effects were explored in vitro. The results showed that CPP-80 was a glucan and its main chain consisted of → 4)-α-D-Glcp-(1 → 4)-β-D-Glcp-(1→, while the end groups α-D-Glcp-(1 → 3)-α-D-Glcp-(1 → and α-D-Glcp-(1 → 6)-α-D-Glcp-(1 → were linked to the main chain by the O-3 of the → 3,4)-α-D-Glcp-(1 → and the O-6 of the → 4,6)-α-D-Glcp-(1 → bonds, respectively. In vitro, CPP-80 had a certain reducing ability and antioxidant activities with the scavenging ratios of 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2′-Azinobis-(3-ethylbenzthiazoline-6-sulphonate) (ABTS) radicals and hydroxyl radicals from about 50 % to more than 80 % at a concentration of 4 mg/mL. Additionally, CPP-80 could immunomodulate RAW264.7 macrophages by boosting phagocytosis and encouraging the release of nitric oxide (NO), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6). Thus, CPP-80 could be used as a promising antioxidant and immunomodulator for food and pharmaceutical applications.